Identificación de bovinos persistentemente infectados y genotipo del virus de la diarrea viral en bovinos de Anta, Cusco, Perú - Valdez G., Edgar (2018)
The aim of this study was to identify persistently infected cattle (PI) and to identify the viral diarrhea virus genotype (BVDV) in cattle of small farmers in five districts of the province of Anta, Cusco, which were negative for antibodies against BVDV (n=558) in a previous study. The identification of the PI animals was carried out in the 558 serum samples of female bovine Holstein, Brown Swiss and Creoles of various ages, by the capture ELISA test. The identification of the viral genotype was carried out in four samples of PI cattle through the RT-PCR real-time. The results showed that 7.2% (40/558) of the cattle were positive for viral antigen in a first analysis, where the antigen was detected in animals older than 6 months up to 5 years in the three breeds. In the second analysis carried out 30 day after in the 40 positives, 30% (12/40) continued to be positive for viral antigen indicating that they were PI animals between 6 months and 4 years in four of the five Anta districts. The prevalence of PI animals in the bovine population sampled in province of Anta was 2.2% (12/558). Real-time RT-PCR showed the amplification of a specific product corresponding to genotype 1 (VDVB-1). There was no amplification of the target sequence of genotype 2.